(untitled) (European Journal of Economics, Finance and Business Development, 2025)
This article examines human capital development in Uzbekistan, its contribution to the economic and social advancement. After regaining independence in 1991, Uzbekistan embarked on the process of changing itself by reinforcing the skills, abilities, and overall welfare of the people. As the nation wrestles with so many economic and social challenges, from labor claims, education reform, and the right to medical care, so much becomes increasingly apparent about having sound human capital development. In this article, the current condition of human capital in Uzbekistan is explored as well as challenges and ways for creating a competitive and adaptable human workforce. By considering the intersection of economic policies and social conditions, the article aims to contribute to the understanding of the critical role played by human capital in shaping Uzbekistan’s destiny.